Ammonia as an effective hydrogen carrier and a clean fuel for solid oxide fuel cells. (15th January 2021) - Wan, Zhijian; Tao, Youkun; Shao, Jing; Zhang, Yinghui; You, Hengzhi
Graphical abstract: Highlights: Ammonia can be produced in a clean manner. Ammonia has added values of globally mature transport and storage networks. Ammonia can be readily decomposed for clean hydrogen production. Ammonia exhibits comparable cell performance with hydrogen in SOFCs. Durability of NH3 -SOFCs can be improved via highly active NH3 decomposition catalyst. Abstract: This contribution delivers the perspectives of ammonia for a clean energy future and examines the potential, achievements, and associated challenges of ammonia for power generation, with a particular focus on ammonia fuelled solid oxide fuel cells (SOFCs). Ammonia, with characteristics of zero-carbon and a high hydrogen content has been increasingly recognised as a clean fuel. The well-established facilities for ammonia production and infrastructures worldwide for storage and transport provide ammonia with indispensable advantages, underpinning its role in enabling a clean energy future. Ammonia can be decomposed into hydrogen and nitrogen free of carbon emission using an appropriate catalyst. Ni-based catalysts are more preferred candidates alternative to Ru-based catalysts with respect to cost and sources. A rational design of catalyst in terms of preparation method, support and promoter is needed to carve out a catalyst that is commercially reliable and affordable. A milestone has been recently achieved using a Ni-based catalyst with long-term stability up to 1000 h. Ammonia also shows promising potentials for clean electricity generation via SOFCs, exhibiting cell performance comparable to that of the hydrogen fuelled counterparts. However, the cell stability is compromised owing to anode degradation, which is primarily attributed to the formation of nickel nitride incurring microstructural deformations in the anode. Feeding SOFCs with pre-decomposed ammonia is then identified to effectively mitigate the nitridation reactions between ammonia and nickel. In such a manner, only a gas mixture consisted of H2 and N2 is fed into the SOFCs, eliminating the reactions of ammonia and the anode.